Lead users method as a source of innovation for E-commerce businesses - Ramos Meoño, Paola Lisbeth (2018)
The objective of the present study is to demonstrate wheter lead user method is more useful than traditional market research method as a source of innovation for e- businesses. Also, to prepared a contribution about the use of lead user method as a source of innovation in e-business, adding new facts and implications that help to improve the actual knowledge about the topic in order to encourage the best practice in the field. Making an interpretative approach in study field, I could find some answers to my research question. Firstly, main characteristics firms expect a new market research method have in order to apply it for their market researches are the use by recommendation and faster in results. Secondly, the choosing of a market research method, must to generate value through the use of KPI´s and reflected in one of the five dimensions of e-commerce value grid. Finally, even Scholars have developed research studies about lead user method and its application to different kind of business since 80´s, few people had listened to lead user method.